Factors Influencing Runner's Choices of Footwear - Ramsey, Codi A.; Lamb, Peter; Ribeiro, Daniel Cury (Frontiers in Sports and Active Living, 2022)
Until the mid 2000s, qualitative research has been virtually absent from running injury research. A handful of studies have been recently published regarding the attitudes and perceptions of runners and coaches towards injury development. Footwear is frequently perceived as a risk factor for running related injuries, but empeirical evidence fails to support such beliefs. The reasons why runners choose specific footwear warrants formal investigation to further understand the links between footwear and running related injuries. This study aimed to investigate the factors influencing runners choices of footwear. Interviews were conducted with 12 runners. Recordings from the interviews were transcribed verbatim and themes were developed using thematic analysis. Findings revealed 15 unique factors that influence runner's choices of footwear for running. These factors were grouped into three main themes: personal footwear characteristic preferences, other people and economic considerations. Runners largely gather information about their footwear choices from past experiences and people they trust and admire. They also emphasized the complexity of footwear choices due to availability and the constant changes preset within the footwear industry. This research adds to the growing body of knowledge to better understand the wider running injury system. Further studies are needed to establish how runners perceptions of their footwear impact injury rates and to develop effective injury prevention strategies.